The The user’s judgment: conceptualization, construction and validation of a measurement scale. Application to the public service - HANINE, Sanae; GHANAM, Ouaffa (Revue du contrôle, de la comptabilité et de l’audit, 2020)
The purpose of this article is to construct and validate a measurement scale of judgment and to test it in the context of public service. The challenge of this research lies in the fact that it is about a princeps work. To our knowledge, there isn’t up today a measurement scale of the “judgment” construct in marketing. Regarding its latent nature, the "judgment" construct can not be directly observed and can be apprehended only through indicators to represent it. In addition to its construction, the psychometric properties of the scale have been verified so that it can be used in future studies and predict the judgment of the public service user. From exploratory and confirmatory analysis through structural equations, we arrive at a measure that presents a reliable and stable structure. The results of the exploratory research highlight seven facets of the user’s judgment following a public servuction: rationality, jugeability, mood, affectivity, familiarity, hedonism and warmth. Confirmatory factor analysis has endorsed a measurement model that demonstrates that the user’s judgment following a public service is composed of five (5) main dimensions: rationality, judgment, affectivity, familiarity and hedonism.